Analysis of the Genome and Metabolome of Marine Myxobacteria Reveals High Potential for Biosynthesis of Novel Specialized Metabolites. Issue 1 (December 2018) - Amiri Moghaddam, Jamshid; Crüsemann, Max; Alanjary, Mohammad; Harms, Henrik; Dávila-Céspedes, Antonio; Blom, Jochen; Poehlein, Anja; Ziemert, Nadine; König, Gabriele; Schäberle, Till
Abstract Comparative genomic/metabolomic analysis is a powerful tool to disclose the potential of microbes for the biosynthesis of novel specialized metabolites. In the group of marine myxobacteria only a limited number of isolated species and sequenced genomes is so far available. However, the few compounds isolated thereof so far show interesting bioactivities and even novel chemical scaffolds; thereby indicating a huge potential for natural product discovery. In this study, all marine myxobacteria with accessible genome data (n = 5), includingHaliangium ochraceum DSM 14365, Plesiocystis pacifica DSM 14875, Enhygromyxa salina DSM 15201 and the two newly sequenced speciesEnhygromyxa salina SWB005 and SWB007, were analyzed. All of these accessible genomes are large (~10 Mb), with a relatively small core genome and many unique coding sequences in each strain. Genome analysis revealed a high variety of biosynthetic gene clusters (BGCs) between the strains and several resistance models and essential core genes indicated the potential to biosynthesize antimicrobial molecules. Polyketides (PKs) and terpenes represented the majority of predicted specialized metabolite BGCs and contributed to the highest share between the strains. BGCs coding for non-ribosomal peptides (NRPs), PK/NRP hybrids and ribosomally synthesized and post-translationally modified peptides (RiPPs) were mostly strain specific. These results were in line with the metabolomic analysis, which revealed a high diversity of the chemical features between the strains. Only 6–11% of the metabolome was shared between all the investigated strains, which correlates to the small core genome of these bacteria (13–16% of each genome). In addition, the compound enhygrolide A, known fromE .salina SWB005, was detected for the first time and structurally elucidated fromEnhygromyxa salina SWB006. The here acquired data corroborate that these microorganisms represent a most promising source for the detection of novel specialized metabolites.